2017
DOI: 10.4067/s0718-58392017000300218
|View full text |Cite
|
Sign up to set email alerts
|

NIR-Prediction of water-soluble carbohydrate in white clover and its genetic relationship with cold tolerance

Abstract: In temperate climates, cold stress constrains productivity of white clover (Trifolium repens L.), the most important perennial forage legume in intensive grazing systems for ruminants. Metabolism of water sugar carbohydrate (WSC) has been proposed as an important trait conferring cold tolerance to white clover. Conventional methodologies for WSC determination are considered high-cost and timeconsuming. Near-infrared (NIR) spectroscopy is a robust, reliable, and high-throughput methodology to estimate chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(53 reference statements)
0
3
1
Order By: Relevance
“…The calibration error obtained in this study for OMD was lower than that reported by Corson et al (1999) in pasture samples with a similar concentration range. The coefficient of determination obtained in this study for WSC was lower than that reported by Alomar et al (2009) and Lobos-Ortega et al (2014) in fresh forage samples and by Inostroza et al (2017) in dried white clover. Finally, the results for R 2 c and the RPD values for the WSC/CP ratio were lower in the present study than those shown by Rivero et al (2014).…”
Section: Nirs Calibration and Validationcontrasting
confidence: 79%
See 1 more Smart Citation
“…The calibration error obtained in this study for OMD was lower than that reported by Corson et al (1999) in pasture samples with a similar concentration range. The coefficient of determination obtained in this study for WSC was lower than that reported by Alomar et al (2009) and Lobos-Ortega et al (2014) in fresh forage samples and by Inostroza et al (2017) in dried white clover. Finally, the results for R 2 c and the RPD values for the WSC/CP ratio were lower in the present study than those shown by Rivero et al (2014).…”
Section: Nirs Calibration and Validationcontrasting
confidence: 79%
“…This technology is broadly accepted as a fast and reliable method for evaluating the nutritional qual-ity of pasture silages (Ibáñez and Alomar, 2008;Restaino et al, 2009), as well as dried and fresh pastures (Cozzolino and Labandera, 2002;Alomar et al, 2009;Burns et al, 2013;Lobos-Ortega et al, 2013;Moscoso and Balocchi, 2016). It has also been used to evaluate how forage sample preparation affects nutrient composition analysis (Alomar et al, 2003), green forage intake and digestibility in ruminants (Decruyenaere et al, 2009), and water-soluble carbohydrates (WSC) in stolon samples of white clover (Inostroza et al, 2017). NIRS has also been used to characterize and quantify isoflavones and phenolic acid contents in red and white clover (Krähmer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, prediction models have been fitted with linear regression techniques that use multivariate inputs (Hernandez et al, 2015; Inostroza et al, 2017). Partial least square (PLS) regression is a widely used methodology to regress predictor data against target prediction traits based on the assumption that the response variables are from a process generated by unobserved latent variables (Rosipal and Krämer, 2006).…”
mentioning
confidence: 99%
“…Thus, the characteristic information of hydrogen-containing groups in organic molecules can be obtained by scanning the near-infrared spectra of samples [ 25 ]. It has been widely used in agriculture, [ 12 , 17 , 19 ], petrochemicals [ 1 , 14 ], food [ 28 ] and pharmaceuticals [ 6 ]. The use of NIR spectroscopy in plant leaf tissue analysis started in the mid-1970s [ 20 ], and there are an increasing number of papers on NIR spectroscopy application on leaf tissues [ 4 , 13 ].…”
Section: Introductionmentioning
confidence: 99%